Production of green gasoline and light olefins by cracking of triglyceride-rich biomass over nano-ZSM-5/SBA-15 analog composites with variable Si/Al ratios - Hoan, Vu Xuan; Sura, Nguyen; Tung, Dang Thanh; Binh, Phan Minh Quoc; Duc, Nguyen Anh; Hunger, Michael; Armbruster, Udo; Martin, Andreas (Petrovietnam Journal, 2016)
Nano-ZSM-5/SBA-15 analog composites (ZSC) with different Si/Al molar ratios were prepared and their performance was evaluated in catalytic cracking of triglyceride-rich biomass. It was found that the initial Si/Al ratio used in the synthesis mixture performance of ZSC catalysts in catalytic cracking of triglyceride-rich biomass.